Paris Agreement 2015: Formulating Indonesia’s Efforts and Challenges in Facing Climate Change - Rizkiawan, Muhammad Faiz Adzani; Prakoso, Andria Luhur (International Journal Labs, 2022)
Background: The Paris Agreement and the rules referring to the agreement play a role in addressing climate change need to implement Indonesian NDCs in every sector in legislation to implement Indonesia's contribution commitment in reducing greenhouse gas emissions as mitigation efforts in the face of climate change that adversely affects the environment and humanity. Aim: Mention the main purpose of the research. Method: Give a brief explanation regarding the method used, along with the sample, data collection technique, and data analysis technique. Findings: The need for spatial arrangements that remain based on environmental functions and on development or land use must be based on the concept of sustainable development and energy transition efforts must be prepared as soon as possible.